Spontaneous rupture of hepatocellular carcinoma: Optimal timing of partial hepatectomy. Issue 10 (October 2019) - Wu, Jing-jing; Zhu, Peng; Zhang, Zhan-guo; Zhang, Bi-xiang; Shu, Chang; Mba'nbo-koumpa, Abdoul-aziz; Zhang, Zhi-wei; Huang, Zhi-yong; Zhang, Wan-guang; Lau, Wan Yee; Chen, Xiao-ping
Abstract: Background: Partial hepatectomy has been used to treat patients with resectable hepatocellular carcinoma (HCC) which spontaneously ruptured. It is still controversial as to whether emergency partial hepatectomy (EmPH) should be carried out at the time of rupture, or the patients should initially be managed by operative or non-operative treatment to stop the bleeding, followed by staged early or delayed partial hepatectomy when the patient's condition becomes stable. Methods: Consecutive 10-year patients with ruptured HCC managed at our center were included in this study. Patients who underwent partial hepatectomy were further subdivided into the EmPH group, the staged early partial hepatectomy (SEPH) group, and the staged delayed partial hepatectomy (SDPH) group. Univariate and multivariate analyses of factors affecting overall survival(OS) were conducted before and after propensity score matching analyses amongst the included patients. OS, postoperative mortality, recurrence free survival (RFS), and peritoneal metastatic rates were compared. The risk factors of peritoneal metastases were determined using the COX regression analysis. Results: The 130 patients who underwent partial hepatectomy were subdivided into the EmPH group (surgery at the time of rupture, n = 30), the SEPH group (surgery ≤ 8 days of rupture, n = 67), and the SDPH group (surgery > 8 days of rupture, n = 33). The remaining 86 patients underwent non-surgical treatment. Partial hepatectomy was an independent predictor of better OS (HR 2.792, P < 0.001). For resectable HCC, the 30-day mortality, OS, and RFS were similar between the EmPH group, and the staged partial hepatectomy (SPH) group which included the patients who underwent SEPH and SDPH. The SEPH group had significantly better OS and RFS. Multivariate COX regression analysis demonstrated that SDPH was strongly associated with postoperative peritoneal dissemination (OR 28.775, P = 0.003). Conclusion: Partial hepatectomy provided significantly better survival than non-surgical treatment for patients who presented with ruptured HCC. Early partial hepatectomy within 8 days of rupture which included EmPH (carefully selected) and SEPH, resulted in significantly less patients with peritoneal dissemination and better long-term survival outcomes (especially RFS) than SDPH.